Efficient solid-phase extraction of oligo-DNA from complex media using a nitrocellulose membrane modified with carbon nanotubes and aminated reduced graphene oxide - Georgian Alin Toader; Daniel Ioan Mihalache; Valentin Titus Grigorean; Elena Alina Chiticaru; Madalina Andreea Pandele; Mariana Ionita (Scientific Reports)
Abstract Oligonucleotides are essential for gene regulation, expression, and disease biomarker identification, yet their small size presents challenges due to lower abundance and increased susceptibility to degradation in biological samples. Addressing these challenges, a novel approach was developed for effective oligonucleotide extraction, consisting of a commercially available nitrocellulose (NC) membrane non-covalently modified with a combination of single-walled carbon nanotubes (SWCNTs) and polyethylene glycol (PEG) aminated reduced graphene oxide (GA). The membrane was evaluated for the extraction of a fluorescent labelled single-stranded deoxyribonucleic acid (ssDNA), with fewer than 30 nucleotides, from complex solutions containing various ionic species (MnCl2, MgCl2, and MnCl2/MgCl2). Fourier transform infrared spectroscopy confirmed successful modification, revealing characteristic peaks of NC, SWCNT, and GA. Raman spectroscopy and X-ray photoelectron spectroscopy showed distinctive changes after the membrane interaction with divalent cations and ssDNA. Scanning electron microscopy revealed morphological changes in the SWCNTs/GA-NC hybrid membrane, showing a smoother surface compared to the porous structure of the unmodified NC membrane. Wettability assays indicated hydrophobic properties for the SWCNT/GA-NC hybrid membrane, with a water contact angle exceeding 110°, contrasting with the hydrophilic nature of the NC membrane, which exhibits a contact angle of 26.7°. Optimal performance of the SWCNTs/GA-NC hybrid membrane was observed when incubated in MgCl2, demonstrating the highest fluorescence emission at approximately 670 relative fluorescence units. This corresponded to the extraction of approximately 781 pg (≈ 16%) of the total oligo-DNA, highlighting the enhanced efficacy of the hybrid material compared to the unmodified NC membrane, which extracted only 318 pg (≈ 7%) of oligo-DNA.